2013
DOI: 10.1128/mcb.00240-13
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Dynamic Dose Responses of Natural Promoters and Single cis Elements upon Osmotic and Oxidative Stress in Yeast

Abstract: Fine-tuned activation of gene expression in response to stress is the result of dynamic interactions of transcription factors with specific promoter binding sites. In the study described here we used a time-resolved luciferase reporter assay in living Saccharomyces cerevisiae yeast cells to gain insights into how osmotic and oxidative stress signals modulate gene expression in a dosesensitive manner. Specifically, the dose-response behavior of four different natural promoters (GRE2, CTT1, SOD2, and CCP1) revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 55 publications
(80 reference statements)
2
32
0
Order By: Relevance
“…It is important to note that the sensitivity of gene expression to a common signal, such as a nutrient or a stress, can be different for specific responsive genes. Here, the chromatin structure and the combination of different cis-regulatory elements in promoters have been implicated in creating characteristic dose sensitivities of yeast genes (14,15). In our present study, we reveal different strategies that ensure an appropriate transcriptional activation corresponding to subtle environmental changes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It is important to note that the sensitivity of gene expression to a common signal, such as a nutrient or a stress, can be different for specific responsive genes. Here, the chromatin structure and the combination of different cis-regulatory elements in promoters have been implicated in creating characteristic dose sensitivities of yeast genes (14,15). In our present study, we reveal different strategies that ensure an appropriate transcriptional activation corresponding to subtle environmental changes.…”
Section: Discussionmentioning
confidence: 88%
“…It is largely unknown how gene regulatory systems adapt to these "suboptimal" signals, mostly because it is experimentally challenging to quantify the dynamic gene expression upon gradually changing stimulation. Here, the recent application of destabilized luciferase reporters for continuous live-cell measurements in yeast turned out to be especially useful (15,38). This real-time survey of gene expression activity reveals the dynamic range of differentially regulated groups of genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TonE/ORE enhancer is also present in other mammalian genes that promote the accumulation of compatible organic osmolytes, including AR (33). Furthermore, salinity-responsive CREs have been identified in yeast (70) and in the quinoa plant 1 and MIPS genes that match a common consensus, which has OSRE activity. The CRE fitting this consensus motif was named OSRE1.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations of the transcriptional response by changes in the cells physiology are not restricted to osmotic stress. It has been recently shown that also oxidative stress, at threshold levels, interferes with efficient transcriptional activation and, more importantly, that mutants in reactive oxygen species detoxification systems show much less dynamic transcriptional responses (28). Thus, the dynamic of a gene expression response to stress is to a great part dependent on cell physiology.…”
mentioning
confidence: 99%